(untitled) (Socio-Economic Development Panorama, 2009)
The transmission mechanism of monetary policy will be strengthened, and the monetary policy objectives attained to a large extent, if the financial system is well-operated and regulated. Credit extended to the private sector in an environment of banking discipline will be instrumental in tapping the productive potentialities and development prospects of the economy. It thereby ushers to inculcate economic growth, generating employment opportunities, and strengthening competitiveness character of the economy. Problems and challenges that weakens the process of smoothly operating the financial institutions, and also devising and implementing the policy and regulatory regime need to be addressed in an earnest manner. This entails that the financial system remains vibrant, efficient and strong. Only then can it work as the catalyst for development of the national economy, functioning in its various dimensions, like investment, saving, economic growth, and stability. Nepal’s progress with respect to financial sector upliftment in general and private sector credit growth in particular is satisfactory in comparison to economies in a similar level of development. The host of development commitments and aspirations in unfolding political environment, and the socio-economic development milieu in Nepal could be transformed into reality only through an arrangement of following an appropriate financing, for which the private sector credit expansion would remain vital. However, much needs to be done to transform economy building on the principles of embracing competitiveness and enhancing credible private sector, and bringing forth fuller compliance with the banking norms. The positive role of all stakeholders for crucial national building task is most desirable. Key words: private; finance; economy; credit; financial resources Socio Economic Development Panorama; Vol. 1; No. 4, 2009; January-June